2008
DOI: 10.4161/cbt.7.10.6585
|View full text |Cite
|
Sign up to set email alerts
|

A combination of Trastuzumab and 17-AAG induces enhanced ubiquitinylation and lysosomal pathway-dependent ErbB2 degradation and cytotoxicity in ErbB2-overexpressing breast cancer cells

Abstract: ErbB2 (or Her2/Neu) overexpression in breast cancer signifies poorer prognosis, yet it has provided an avenue for targeted therapy as demonstrated by the success of humanized monoclonal antibody Trastuzumab (Herceptin™). Resistance to Trastuzumab and eventual failure in most cases, however, necessitate alternate ErbB2-targeted therapies. HSP90 inhibitors such as 17-allylaminodemethoxygeldanamycin (17-AAG), potently downregulate the cell surface ErbB2. While the precise mechanisms of Trastuzumab or 17-AAG actio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
81
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(88 citation statements)
references
References 38 publications
7
81
0
Order By: Relevance
“…Accordingly, inhibition of Hsp90 induces proteasomal degradation of HER2 and suppresses growth of breast cancer cells and breast cancer xenograft tumors in vivo (18)(19)(20)(21)(22). The Hsp90 inhibition-mediated degradation of HER2 is enhanced with the addition of trastuzumab (23), and an early clinical trial that combined the Hsp90 inhibitor 17-AAG with trastuzumab has shown signs of efficacy among patients with trastuzumab refractory breast cancer (23,24). 17-AAG is a potent inhibitor of Hsp90, but its clinical development has been hampered by pharmacologic liabilities, including poor aqueous solubility, which could limit patient safety and the therapeutic index.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, inhibition of Hsp90 induces proteasomal degradation of HER2 and suppresses growth of breast cancer cells and breast cancer xenograft tumors in vivo (18)(19)(20)(21)(22). The Hsp90 inhibition-mediated degradation of HER2 is enhanced with the addition of trastuzumab (23), and an early clinical trial that combined the Hsp90 inhibitor 17-AAG with trastuzumab has shown signs of efficacy among patients with trastuzumab refractory breast cancer (23,24). 17-AAG is a potent inhibitor of Hsp90, but its clinical development has been hampered by pharmacologic liabilities, including poor aqueous solubility, which could limit patient safety and the therapeutic index.…”
Section: Introductionmentioning
confidence: 99%
“…However by 60 min, the Dox fluorescence was found in the nucleus, confirming diffusion of DOX from the lysosomes, presumably following disintegration under the lysosomal pH, redox conditions and lysosomal proteases, such as Cathepsins. Previous studies from our lab has shown that BIC nanogels with crosslinked ionic cores can be selectively endocytosed into cancer cells, which lack tight epithelial cell junctions, in contrast to normal epithelial cells that form tight junctions (7). The internalization route appeared to be predominantly via the caveolar pathway.…”
Section: Cellular Uptake Of 17-aag and Dox Encapsulated In Nanogels Imentioning
confidence: 78%
“…GA is an inhibitor of HSP90 and is known to down-regulate HER2 levels by diverting endosomal trafficking of HER2 from recycling back to membrane surface [23,34]. A combination study of trastuzumab and 17-AAG (17-(allylamino)-17-demethoxygeldanamycin) showed enhanced HER2 down-regulation [35]. Since uptake of trastuzumab-drug conjugates is dependent on binding of HER2 for internalization, down-regulation of HER2 by GA may decrease uptake of trastuzumab-GA conjugate.…”
Section: Discussionmentioning
confidence: 99%